BEHAVIORAL RISK FACTORS ASSOCIATED WITH SEXUAL DYSFUNCTION IN MEN - Volodymyr I. Trishch; Oryna Z. Detsyk (Клінічна та профілактична медицина, 2025)
Introduction. Sexual health is a fundamental part of everyone's physical, mental and social well-being. Despite the considerable interest of scientists in studying the impact of behavioral risk factors on sexual dysfunctions, most of them are fragmented and address specific aspects of the problem. However, comprehensive research on this issue is still lacking.